2018
DOI: 10.15446/acag.v67n4.60023
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient solution salinity effect of greenhouse melon (Cucumis melon L. cv. Néctar)

Abstract: In Mossoró-RN, which is part of the semi-arid region of Brazil, a large part of the country’s melon production is concentrated, whose great potential is currently limited by water quality due to salt concentration. Therefore, the objective of this work was to investigate the use of saline nutritive solutions in the irrigation of greenhouse melon (Cucumis melo L. cv. Néctar) culture in coconut fiber. The experiment was carried out using a randomized block design with a 5 x 2 factorial arrangement, with four rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
4
5
0
Order By: Relevance
“…The lack of a salinity effect on the firmness of the melon pulp observed in the present study is in agreement with results presented by other authors (Pereira et al, 2017;Dias et al, 2018). This is an essentially important attribute when it comes to postharvest handling, as firmer fruits better resist mechanical injuries during transport and marketing operations.…”
Section: Fruit Quality Componentssupporting
confidence: 93%
See 4 more Smart Citations
“…The lack of a salinity effect on the firmness of the melon pulp observed in the present study is in agreement with results presented by other authors (Pereira et al, 2017;Dias et al, 2018). This is an essentially important attribute when it comes to postharvest handling, as firmer fruits better resist mechanical injuries during transport and marketing operations.…”
Section: Fruit Quality Componentssupporting
confidence: 93%
“…In the present study, IC showed the same response as that described by Dias et al (2018), who reported a reduction in this variable at salinity levels greater than 3.0 dS m -1 . Queiroz (2016) worked with 'Gália' melon grown in fiber substrate and fertigated under K concentrations and found an increase in IC in response to the increasing K rates; however, no salinized nutrient solution was used.…”
Section: Fruit Yield Componentssupporting
confidence: 90%
See 3 more Smart Citations